Social and behavioral predictors of two-doses 4CMenB vaccine series among adolescents enrolled in a cluster randomized controlled trial in Australia. Issue 1 (31st December 2022) - Mohammed, Hassen; McMillan, Mark; Marshall, Helen S.
ABSTRACT: This study aimed to determine social and behavioral predictors of completing a course of 4CMenB vaccine in adolescents in a parallel cluster randomized controlled trial enrolling secondary school students (approximately 15–18 years of age) in South Australia. Participating schools were randomized to vaccination at baseline (intervention) or 12 months (control). Students assigned to the intervention group were excluded because they have received the first dose of 4CMenB vaccine at baseline. Logistic regression models examined factors associated with non-vaccination or incomplete 4CMenB doses. The study population comprised 11391 students. Overall, 8.3% (n = 946) received no doses and 91.7% (n = 10445) at least one dose. Of 10445 students who initiated their primary dose, 1334 (12.8%) did not complete the two-dose course. The final adjusted model indicated factors associated with non-vaccination in school students were older age (adjusted odds ratio; aOR 7.83, 95% CI: 4.13–14.82), smoking cigarettes (aOR 3.24, 95% CI: 1.93–5.44), exposure to passive smoke (aOR 2.64, 95% CI: 1.48–4.71), Aboriginal or Torres Strait Islander (aOR 1.77, 95% CI: 1.23–2.55), smoking water pipes (aOR 1.94, 95% CI:1.28–2.92), low socioeconomic status (aOR 1.77, 95% CI:1.21–2.60), attending government schools (aOR 1.76, 95% CI: 1.28, 2.43) and participating in intimate kissing (aOR 1.40, 95% CI:1.10–1.79). Multivariable analysis for incomplete vaccination yielded similar findings. Social and behavioral predictors of non-vaccination or incomplete MenB doses were also known risk factors for carriage of Neisseria meningitidis . Immunization strategies to improve MenB vaccination completion need to be tailored to social behavior of adolescents.